Synthesis and Characterization of Nickel(II) Imprinted Polymers as a Selective Adsorbent for Nickel(II) Ions - Siska Ela Kartika; Putri Septiani Hariyanto; Armeida D. R. Madjid; Sonita Afrita Purba Siboro; Roni Sujarwadi (Jurnal Kimia Sains dan Aplikasi, 2025)
The rapid expansion of nickel mining in Indonesia, driven by the growing demand for electric vehicle batteries, has raised concerns about the environmental and health impacts of nickel pollution. This study presents the synthesis and characterization of a highly selective adsorbent, Nickel(II) Imprinted Polymer (Ni(II)-IPs), for the monitoring and removal of Ni(II) ions. Ni(II)-IPs were synthesized using precipitation polymerization by imprinting the Ni(II)-8-hydroxyquinoline complex into a polymer matrix through the polymerization of methacrylic acid and ethylene glycol dimethacrylate. Successful imprinting and subsequent leaching of Ni(II) ions using HNO3 were confirmed by FTIR, SEM, and EDX characterization. Adsorption studies revealed that Ni(II)-IPs exhibit a high adsorption capacity of 70.26 mg/g at pH 7 within a short contact time of 15 minutes. Moreover, Ni(II)-IPs demonstrated excellent selectivity towards Ni(II) ions in the presence of competing ions, with relative selectivity coefficients of 1.20, 1.24, and 1.31 for Ni(II)/Cu(II), Ni(II)/Co(II), and Ni(II)/Pb(II), respectively. These findings highlight the potential of Ni(II)-IPs as an efficient and selective adsorbent for monitoring and removing Ni(II) ions from complex aqueous matrices, thereby addressing growing concerns about nickel pollution in Indonesia and beyond.